Annotated translation of the Aero Club del Ecuador website as a contribution to the internationalization of the Ecuadorian Aviation Field. - Alchundia Castro, Pedro Manuel (2015)
The following annotated translation is based on general and aeronautical terms; it is an endeavour to contribute not only to a specific Ecuadorian flight school, Aero Club del Ecuador, but also to the Ecuadorian aviation field. Its website, www.aeroclubdelecuador.com.ec presents a monolingual system through the webpages, which limits itself to the global market in Latin America and any other area where Spanish-speaking countries are found. At the moment ACE has few international student pilots enrolled for this year. Although, they are foreigners, they are from neighboring countries of Ecuador and ACE is in the pursuit of new further territories. The aim of this website translation followed by an accurate level of localization is to provide a great advantage for people, who are in other places in the world and would like to learn how to fly and become a pilot with international certifications that are backed by the ICAO (International Civil Aviation Organization), DAC (Direccion General de Aviacion Civil) and other international regulations. Furthermore, it will create an interest to visit and see exotic landscapes that make our country unique. Also, ACE is looking for the increase of student pilots and stand out from others flight schools in order to obtain more capital to improve the education. Moreover, in this render of the website strategic images will be interpreted under appropriate localization guidelines. Another aim is to boost the English language at the flight school by being exposed as an international flight school on social media becoming more efficient and competitive for new challenges and avoiding language barriers that may exist. It is important important to mention that this annotated translation will become guidance for visitors to choose the type of flight training program offered by ACE and requirements needed to meet before the enrollment.